From Lysosomal Storage Disorders to Parkinson's Disease – Challenges and Opportunities - Mächtel, Rebecca; Boros, Fanni Annamaria; Dobert, Jan; Arnold, Philipp; Zunke, Friederike (Journal of Molecular Biology, 2023)
Lysosomes are specialized organelles with an acidic pH that act as recycling hubs for intracellular and extracellular components. They harbour numerous different hydrolytic enzymes to degrade substrates like proteins, peptides, and glycolipids. Reduced catalytic activity of lysosomal enzymes can cause the accumulation of these substrates and loss of lysosomal integrity, resulting in lysosomal dysfunction and lysosomal storage disorders (LSDs). Post-mitotic cells, such as neurons, seem to be highly sensitive to damages induced by lysosomal dysfunction, thus LSDs often manifest with neurological symptoms. Interestingly, some LSDs and Parkinson's disease (PD) share common cellular pathomechanisms, suggesting convergence of aetiology of the two disease types. This is further underlined by genetic associations of several lysosomal genes involved in LSDs with PD. The increasing number of lysosome-associated genetic risk factors for PD makes it necessary to understand functions and interactions of lysosomal proteins/enzymes both in health and disease, thereby holding the potential to identify new therapeutic targets. In this review, we highlight genetic and mechanistic interactions between the complex lysosomal network, LSDs and PD, and elaborate on methodical challenges in lysosomal research.
CRIS-Team Scopus Importer:2023-03-24
Keywords: lysosomal enzymes; lysosomal storage disorder; lysosome; neurodegeneration; Parkinson's disease